Wound Healing New insights into Ancient Challenges - Adrian Alexandrescu, Vlad (IntechOpen, 2016)
Outstanding scientific advances over the last decades unceasingly reveal real complexity of wound-healing process, astonishing in its staged progression, as life is unfolding itself. This natural course of tissue repair seems to bear thousands of overlapping molecular and macroscopic processes that nowadays only start to unfold to our knowledge. The present volume collecting recent scientific references proposes to readers a two-folded audacious goal. First, an updated design of intimate cellular mechanisms is entailed in tissue regeneration that emanates from the first section of the book. Next, a multidisciplinary therapeutic perspective that focuses on macroscopic healing throughout the second part of this work adds clinically integrated observation. Practical diagnostic and treatment information is appended in each chapter that may equally help experienced clinicians or dedicated students and researchers in broadening essential breaking points of their work. It is the wish of all multidisciplinary experts who gather prominent author's panel of this volume to incorporate latest medical reports and compel limits of current understanding for better tissue regeneration, limb salvage, and improved quality of life of our patients.